Dialog sodobnih literarnih ustvarjalcev z večkulturnostjo evropske družbe - Curk, Mateja (Slavistična revija, 2017)
In this article, the characteristics of the social profile are attributed to the bilingual narrator in Andrej E. Skubic and Goran Vojnović's works of prose. Examples of contemporary works of prose are used to problematize the link that frequently exists between the social profile of the first-person narrator and the personal profile of the author. As regards the comparable characteristics of the social profiles of bilingual narrators who identify with a community of immigrants' descendants in the works of authors whose personal profiles do not coincide with the profiles of the former, the article argues that the dialogue established with social reality draws on the multicultural image of Slovenian society - as a reflection of wider contemporary European society.
Keywords: "Čefurji raus!"; "Fužinski bluz"; družbeni profil; novel; prvoosebni pripovedovalec; roman; Skubic, Andrej E., 1967-; Slovene literature; slovenska književnost; slovenski pisatelji; večkulturnost; Vojnović, Goran, 1980-